2009
DOI: 10.1007/s00441-009-0860-4
|View full text |Cite
|
Sign up to set email alerts
|

Localization of poly(A)+ RNA and mRNA export factors in interchromatin granule clusters of two-cell mouse embryos

Abstract: Interchromatin granule clusters (IGCs), also known as nuclear speckles, splicing factor compartments, or SC35-domains, are one of the most universal nuclear organelles of the cell. We have used two-cell mouse embryos as an experimental system to study the possible association of poly(A)(+) RNA and factors involved in RNA export (Tip-associated protein [TAP] and heterogenous nuclear ribonucleoprotein A/B [hnRNP A/B]) with IGCs. Poly(A)(+) RNA was localized by microinjections of 2'-O-Me(U)(22) probes conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Thus, correlation between the size of IGCs and transcriptional activity differs in early mammalian embryos and somatic cells. However, experimental transcription inhibiting in late 2-cell mouse embryos provokes the appearance of extremely large IGCs/speckles [21, 31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, correlation between the size of IGCs and transcriptional activity differs in early mammalian embryos and somatic cells. However, experimental transcription inhibiting in late 2-cell mouse embryos provokes the appearance of extremely large IGCs/speckles [21, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…There are only scarce data on IGCs at the initial stages of embryogenesis [1820]. However, our previous observations [21] have demonstrated some distinctions of IGCs in early mouse embryos from classical speckles described in somatic cells.…”
Section: Introductionmentioning
confidence: 88%
“…Previous reports regarding the spatial organization of successive pre-mRNA maturation stages indicate that the main sites of poly(A) RNA and mRNA concentration in the nucleus are dynamic, irregular structures termed speckles (Carter et al 1991, 1993; Wei et al 1999; Molenaar et al 2004; Xie and Pombo 2006; Ishihama et al 2008; Bogolyubova et al 2009; Batalova et al 2010). We have previously demonstrated that in larch, poly(A) RNA localizes in speckles, but this occurred independently from the RNA accumulation in nuclear bodies (Kołowerzo et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our group, we also studied nuclear distribution of some representative proteins constituting the exon-exon junction complex (EJC) [45, 46, 67]. The EJC is a multiprotein complex that is loaded onto mRNA during splicing at a precise position upstream of exon-exon junctions [68].…”
Section: Some Proteins Of the Exon-exon Junction Complexmentioning
confidence: 99%
“…Possible association of NXF1/TAP with nuclear speckles was also studied at the 2-cell stage [45]. In transcriptionally active embryos, NXF1/TAP was detected in the vicinity of the IGCs/speckles rather than inside these nuclear domains.…”
Section: Some Proteins Of the Exon-exon Junction Complexmentioning
confidence: 99%